Identifying Active Sites of Nitrogen‐Doped Carbon Materials for the CO2 Reduction Reaction. (14th April 2018) - Liu, Song; Yang, Hongbin; Huang, Xiang; Liu, Linghui; Cai, Weizheng; Gao, Jiajian; Li, Xuning; Zhang, Tao; Huang, Yanqiang; Liu, Bin
Abstract: Nitrogen‐doped carbon materials are proposed as promising electrocatalysts for the carbon dioxide reduction reaction (CRR), which is essential for renewable energy conversion and environmental remediation. Unfortunately, the unclear cognition on the CRR active site (or sites) hinders further development of high‐performance electrocatalysts. Herein, a series of 3D nitrogen‐doped graphene nanoribbon networks (N‐GRW) with tunable nitrogen dopants are designed to unravel the site‐dependent CRR activity/selectivity. The N‐GRW catalyst exhibits superior CO2 electrochemical reduction activity, reaching a specific current of 15.4 A gcatalyst −1 with CO Faradaic efficiency of 87.6% at a mild overpotential of 0.49 V. Based on X‐ray photoelectron spectroscopy measurements, it is experimentally demonstrated that the pyridinic N site in N‐GRW serves as the active site for CRR. In addition, the Gibbs free energy calculated by density functional theory further illustrates the pyridinic N as a more favorable site for the CO2 adsorption, *COOH formation, and *CO removal in CO2 reduction. Abstract : A 3D nitrogen‐doped graphene nanoribbon network is constructed by the chemical pyrolysis with high CO2 electrochemical reduction performance. The pyridinic N site is proved to be the active site by experimental and density functional theory calculations.